Robust beamforming based on transmit power analysis for multiuser multiple-input–single-output interference channels with energy harvesting - Zhu, Zhengyu; Wang, Zhongyong; Chu, Zheng; Gao, Xiangchuan; Zhang, Yanbin; Cui, Jianhua (IET communications, 2016)
In this study, the authors study the robust transmit beamforming and receive power splitting design for simultaneous wireless information and power transfer in multiuser multiple-input–single-output interference channel with imperfect channel-state information at the transmitter. Following the worst-case model, they minimise the average total transmit power subject to a set of energy harvesting constraints and signal-to-interference-and-noise ratio constraints. On the basis of the Lagrangian multiplier method, they propose a robust design method based on tight bounds that is able to achieve an approximate optimum. To reduce the complexity, they transform this original problem into a relaxed semi-definite programming problem based on loose bounds, which can be solved efficiently. It is shown from simulation results that their proposed methods outperform the non-robust scheme.